Analisis Model Keputusan Berkunjung Ulang terhadap Loyalitas Pelanggan - Primasari, Dyah; Farida, Naili; Kartini, Apoina (HIGEIA (Journal of Public Health Research and Development), 2021)
Healthcare industry has a challenge of transforming customers satisfied into customers loyalty. The increasing number of hospitals in Central Java pushed the hospital to try to remain a community choice. Hospitals need to make new services to maintaining the company. This study aimed to analyze the influence of service quality, religiosity, and customer value which were mediated by revisit toward customer loyalty at the S beauty clinic in Semarang. The respondents were all customers who have been doing treatment or buying beauty products at S beauty clinic. 99 respondents were selected using accidental sampling. The data were analyzed by Partial Least Square (PLS). The results showed that there was an influence of customer’s value (T-statistic = 4.570) toward revisit decision, but ini the context of service quality (T-statistic = 0.362) and religiosity (T-statistic = 1.181) did not give any influence toward revisit decision. Whereas, the revisit decision (T-statistic = 15.598) gave influence toward customer loyalty. This indicates that the patient who are revisit is loyal customer to S Beauty Clinic. Keywords: Revisit, Customer Loyalty